Nietzsche’s Ideal of Wholeness - Zamosc, Gabriel (2015)
In this paper I investigate Nietzsche’s ideal of wholeness or unity. The consensus among commentators is that this ideal consists in the achievement of psychic integration in a person whereby the various parts of the agent’s mind are restructured into a harmonious whole. Against this prevalent reading, I argue that Nietzschean wholeness concerns cultural integration: a person becomes whole by pursuing the ideal of freedom and humanity in himself and in all, an ideal that transcends national boundaries and that is universal in scope. For Nietzsche, the pursuit of this ideal makes a person into a piece of fate or primal law, that is, it makes him necessary for all that is and that is yet to come. In this way, the person who becomes whole finds redemption from the meaninglessness of existence. Instead of allowing his life to become a mindless act of chance, this person manages to project his energies into the future in the form of the very ideal he fought and aspired to realize while alive – an ideal that is being perpetually renewed and guaranteed for all within the suprapersonal community that is made up of those genuine fighters of culture who became whole.